2002
DOI: 10.1074/jbc.m207105200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Molecular Interactions of Oversulfated Chondroitin Sulfate E with Various Heparin-binding Growth Factors

Abstract: We previously observed that the cortical neuronal cell adhesion mediated by midkine (MK), a heparin (Hep)-binding growth factor, is specifically inhibited by oversulfated chondroitin sulfate-E (CS-E) (Ueoka, C., Kaneda, N., Okazaki, I., Nadanaka, S., Muramatsu, T., and Sugahara, K. Proteoglycans (PGs)1 that bear heparan sulfate (HS) glycosaminoglycan side chains have attracted much attention because of the demonstration of the involvement of HS in the developmental processes and specific signaling pathways (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
257
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 309 publications
(273 citation statements)
references
References 73 publications
12
257
0
4
Order By: Relevance
“…Among the CS variants, CS-E and CS-D, which are highly sulfated, promote the outgrowth of neurites in embryonic mouse hippocampal neurons [23]. These two CS variants also show strong affinity to some growth factors, such as fibroblast growth factors and bone morphogenetic proteins (BMPs) [24,25]. CS-E enhances osteoblast differentiation by binding to BMP-4, which is an essential growth factor for chondrogenic differentiation [26].…”
Section: Discussionmentioning
confidence: 99%
“…Among the CS variants, CS-E and CS-D, which are highly sulfated, promote the outgrowth of neurites in embryonic mouse hippocampal neurons [23]. These two CS variants also show strong affinity to some growth factors, such as fibroblast growth factors and bone morphogenetic proteins (BMPs) [24,25]. CS-E enhances osteoblast differentiation by binding to BMP-4, which is an essential growth factor for chondrogenic differentiation [26].…”
Section: Discussionmentioning
confidence: 99%
“…The binding of growth factors (including FGF-2) to HS and DS requires IdoUA residues (43,44). However, CS-E exclusive of IdoUA also exhibits specific interactions of high affinity with various heparin-binding growth factors (13), implying the importance of the E unit and the sulfation patterns as well. CS/DS hybrid chains from embryonic pig brain bind various growth factors (16), and hybrid chains of endocan DS-PG on the endothelial surface are also instrumental in bringing about hepatocyte growth factor-me- g as uronic acid) were digested extensively with chondroitinase ABC (A), AC-I (B), or B (C), and the individual digests were labeled with the fluorophore 2-AB and analyzed by anion-exchange HPLC on a PA-03 column using a 16 -530 mM NaH 2 PO 4 gradient over a 1-h period.…”
Section: Discussionmentioning
confidence: 99%
“…Digestions with various chondroitinases revealed the involvement of both GlcUA and IdoUA. CS/DS chains bind heparin-binding growth factors (13,16) and may act as receptors or coreceptors in addition to conventional HS chains, and such growth factors may, in turn, be involved in the neuritogenic mechanism of CS/DS chains in vivo. Indeed, Bao et al 2 recently identified PTN as an endogenous ligand for embryonic pig brain CS/DS chains and observed stimulation of the neuritogenic activity of these chains by exogenously added PTN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the squid cartilage CS-E [GlcAβ1,3GalNAc(4S,6S)β1,4] has been found to interact with various heparin-binding growth factors. 49 CS octa or larger oligosaccharides with at least three continuous CS-E sequences have been shown to bind to type V collagen. 50 Purified squid N-acetylgalactosamine 4-sulfate 6-O-sulfotransferase (GalNAc4S-6ST) has been used in enzymatic synthesis of CS-E from CS-A [GlcAβ1,3GalNAc(4S)β1,4], converting half of GalNAc(4SO 4 ) residues to GalNAc(4,6-SO 4 ) residues.51 This enzyme can also catalyze the synthesis of oversulfated DS IdoAα1,3GalNAc(4S,6S)β1,4 units when DS IdoAα1,3GalNAc(4S)β1,4 is used as the substrate.…”
Section: Glycosaminoglycansmentioning
confidence: 99%